The Impact of Financial Capability on Well-Being: Serial Mediation by Anxiety and Behavior among Indonesian Retail Investors - Rahmadhani, Sari Nuzullina; Nasution , Muhammad Dharma Tuah Putra (Jurnal Ilmiah Akuntansi Kesatuan, 2025)
In recent years, attention to individual financial well-being has increased significantly, driven by the increasing complexity of financial decisions amidst global economic dynamics. This study examines the relationship between financial capability, financial anxiety, and financial behavior in determining financial well-being among retail investors in the Indonesian capital market. This study uses a quantitative approach utilizing survey data from 200 retail investors and analyzes the data through Structural Equation Modeling Partial Least Squares (SEM-PLS). The findings reveal that financial capability negatively impacts financial anxiety while positively impacting financial behavior. Furthermore, financial behavior significantly impacts financial well-being. This study establishes a serial mediation effect where financial capability influences financial well-being through sequential mediation of financial anxiety and financial behavior. This study contributes to the literature by empirically testing a serial mediation model in the context of retail investment and underscoring the important role of psychological factors in individuals' financial decision-making processes in the capital market.